Inhibition of Lipid Accumulation in Skeletal Muscle and Liver Cells: A Protective Mechanism of Bilirubin Against Diabetes Mellitus Type 2 - Hana, Claudia A.; Klebermass, Eva-Maria; Balber, Theresa; Mitterhauser, Markus; Quint, Ruth; Hirtl, Yvonne; Klimpke, Antonia; Somloi, Sophie; Hutz, Juliana; Sperr, Elisabeth; Eder, Paulina; Jašprová, Jana; et al. (Frontiers in Pharmacology, 2021)
Ectopic lipid accumulation in skeletal muscle and liver drives the pathogenesis of diabetes mellitus type 2 (DMT2). Mild hyperbilirubinaemia has been repeatedly suggested to play a role in the prevention of DMT2 and is known for its capacity to shape an improved lipid phenotype in humans and in animals. To date, the effect of bilirubin on lipid accumulation in tissues that are prone to ectopic lipid deposition is unclear. Therefore, we analysed the effect of bilirubin on lipid accumulation in skeletal muscle and liver cell lines. C2C12 skeletal mouse muscle and HepG2 human liver cells were treated with physiological concentrations of free fatty acids (FFA) (0.5mM and 1mM) and unconjugated bilirubin (UCB) (17.1µM and 55µM). The intracellular presence of UCB upon exogenous UCB administration was confirmed by HPLC and the lipid accumulation was assessed by using Nile red. Exposure of both cell lines to UCB significantly reduced lipid accumulation by up to 23% (p≤0.001) in HepG2 and by up to 17% (p≤0.01) in C2C12 cells at 0.5h and 5h under hypoglycaemic conditions. Simultaneously, UCB slightly increased FFA uptake in HepG2 cells after 0.5h and 5h and in C2C12 cells after 12h as confirmed by gas chromatographic analyses of the remaining FFA content in the incubation media. The effects of UCB on lipid accumulation and uptake were abolished in the presence of higher glucose concentrations. Monitoring the uptake of a radiolabelled glucose analogue ([18F]FDG: 2-deoxy-2-[18F]fluoro-D-glucose) into both cell types further indicated higher glucose consumption in the presence of UCB. In conclusion, our findings show that UCB considerably decreases lipid accumulation in skeletal muscle and liver cells within a short incubation time of max. 5h which suggests that mildly elevated bilirubin levels could lower ectopic lipid deposition, a major key element in the pathogenesis of DMT2.